The Knowledges Of Traditional Irrigation In The Oasis Of Kerzaz In Southwest Algerian: Legacy And Development - Rezzoug, C.; Remini, B.; Hamoudi, S. (University of Eloued جامعة الوادي, 2017)
In the valley of Saoura, the demand for water for irrigation has increased significantly and rapidly, it requires mobilization and rational and intensive use of all existing water sources like the groundwater which are the only source of drinking water supply and irrigation in the region and the protection of the large vein that feeds the Saoura and bearing his name "oued Saoura". Oasis Kerzaz is amongst the the most celebrated oasis and the biggest of valley of Saoura , it now suffers from several impediments to their development as: the scarcity of irrigation water, land abandonment, the silting up, the chunking and the exiguity of agricultural land, the food nature of agricultural activity and incurable diseases of crops.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: palm grove; well; Chadouf; Khottara; motorpump; Saoura.